2013
DOI: 10.1002/aic.14202
|View full text |Cite
|
Sign up to set email alerts
|

La0.6Sr0.4Co0.8Ga0.2O3‐δ (LSCG) hollow fiber membrane reactor: Partial oxidation of methane at medium temperature

Abstract: In this study, La 0.6 Sr 0.4 Co 0.8 Ga 0.2 O 3-d (LSCG) hollow fiber membrane reactor was integrated with Ni/LaAlO 3 -Al 2 O 3 catalyst for the catalytic partial oxidation of methane (POM) reaction. The process was successfully carried out in the medium temperature range (600-800 C) for reaction of blank POM with bare membrane, catalytic POM reaction and swept with H 2 :CO gas mixture. For the catalytic POM reaction, enhancement in selectivity to H 2 and CO is obtained between 650-750 C when O 2 :CH 4 <1. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 62 publications
0
19
1
Order By: Relevance
“…Kathiraser et al [215] reported a study on the La 0.6 Sr 0.4 Co 0.8 Ga 0.2 O 3-δ hollow fiber membrane. The authors introduced the Ga 3+ cation in the membrane structure to improve its mechanical stability.…”
Section: Partial Oxidation Of Methane (Pom)mentioning
confidence: 99%
“…Kathiraser et al [215] reported a study on the La 0.6 Sr 0.4 Co 0.8 Ga 0.2 O 3-δ hollow fiber membrane. The authors introduced the Ga 3+ cation in the membrane structure to improve its mechanical stability.…”
Section: Partial Oxidation Of Methane (Pom)mentioning
confidence: 99%
“…Kathiraser et al [166] and Kathiraser and Kawi [167] showed a composite Lanthanum-Strontium-Cobalt-Gallium oxide membrane-type reactor to produced up to 94% and 73% conversion of methane and carbon dioxide, respectively, during dry reforming over Ni-supported and La-supported Al 2 O 3 catalyst system at moderate temperatures. Catalyst was completely stable with no detectable coke deposition for 160 h period.…”
Section: Effect Of Reactor Designmentioning
confidence: 99%
“…If not oxidized, carbon remains attached to an otherwise active site and slows down the surface reaction in a manner similar to catalyst poisoning . Conversely, carbon oxidation can follow either partial oxidation or combustion depending on catalysts and reactant flow rates . As lattice oxygen is more active than gas‐phase oxygen species in oxidizing carbon species, the oxygen flux from water thermolysis on the feed side can affect the relative concentrations of these carbon species.…”
Section: Adding a Porous Layer For Performance Enhancementmentioning
confidence: 99%
“…To increase the oxygen flux further, we added a catalyst to the porous layer on the sweep side to accelerate the surface reaction. Nickel catalysts are reported to be one of the most effective base metal catalysts for POM in both packed bed or membrane reactors . While solid carbon is prone to form on nickel from methane decomposition, it is found that the active lattice oxygen from the catalysts or the support can facilitate the oxidation of surface carbon or soot .…”
Section: Further Enhancements Using a Nickel Catalystmentioning
confidence: 99%